PENGARUH DOSIS KOMPOS FERMENTASI DAN PENGGUNAAN PUPUK HAYATI MIKORIZA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris. L) - Putri Amilda; Aman Suyadi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
Research has been conducted in Bojongsari Village, Kembaran Subdistrict Banyumas Regency Central Java on ± 3 month. The aim of research: To know dose of fermentation compost was best influenced on growth and yield of French bean. To know treatment of natural fertilizer mycorrhiza on influenced on growth and yield of French bean. To know the interaction’s effect between fermentation compost dose and usage of biological fertilizer micorrhyze on growth and yield of French bean. This research represents polibag experiment with factorial pattern. Used design was Randomized Block Design (RBD) with four times replications. Each treatment plot number was 24. Each experimental plot comprised of three plants then total number of plant was 72. Tested factors were fermentation compost dose (15.000 kg/ha or 75 gram/polibag, 20.000 kg/ha or 100 gr/polibag, 25.000 kg/ha or 125 gram/polibag) and usage biological fertilizer mycorrhiza (without mycorrhiza and use mychorriza). Research result showed that treatment of fermentation compost providing significant effect on number of pods. While on other variable studied such as plant length, the amount of leaf, the weight of the wet upper plant, the weight of fresh root and pods weight was not significantly influenced. Treatment of fermentation compost with dose of 125 gram/polibag represent best fermentation compost dose at this research. Treatment of biological fertilizer mycorrhiza was not significantly influenced on entire observed variables that where plant length, leaf number, the weight of the wet upper plant, the weight of fresh root and pods weight. There was interaction between treatment of compost fertilizer combination and natural fertilizer mychorrhiza on growth and yield of French bean at observed variable that were lower bunch weight that significantly different and not significantly different in plant length, leaf number, the weight of the wet upper plant, the weight of fresh root and pods weight. Key words: Fermentation compost, mycorrhiza, french bean